Defining geological viability criteria for CO2 and hydrogen storage in depleted oil and gas fields (Research, Society and Development, 2024)
This study focuses on how depleted oil and gas fields can be used as geological reservoirs to support the shift towards decarbonization and sustainable, low-carbon energy systems. These reservoirs, integral to CO2 and hydrogen storage, are pivotal in harmonizing the dual objectives of environmental conservation and energy transition. We delve into the characteristics of these depleted fields, evaluating their suitability for both CO2 and hydrogen storage, each serving distinct yet complementary decarbonization roles. CO2 storage, facilitated through carbon capture and storage (CCS) technology, aims to diminish atmospheric CO2 levels, thereby mitigating climate change. In parallel, hydrogen storage in these depleted fields emerges as a strategic solution for managing the intermittency of renewable energy sources like wind and solar power. Our study starts from the premise of using depleted oil and gas fields, assessing their potential and challenges for CO2 and hydrogen storage. We define essential criteria for evaluating the feasibility of depleted reservoirs, considering the distinct nature of CO2 and hydrogen. The literature review supported the analysis developed in this research, leading to the creation of three categories of criteria — structural and tectonic, storage and containment, and impact and reactivity — which provide a comprehensive framework for evaluating the viability of these reservoirs for both gases. Through this perspective, this research aims to systematically assess how specific factors such as porosity and permeability impact the efficacy of gas storage, thereby identifying essential parameters for optimizing storage solutions for either CO2 or hydrogen.